2014
DOI: 10.1179/2049396714y.0000000083
|View full text |Cite
|
Sign up to set email alerts
|

The influence of demographics and working conditions on self-reported injuries among Latino day laborers

Abstract: Background: The majority of day laborers in the USA are Latinos. They are engaged in high-risk occupations and suffer high occupational injury rates. Objectives: To describe on-the-job injuries reported by Latino day laborers, explore the extent that demographic and occupational factors predict injuries, and whether summative measures for total job types, job conditions, and personal protective equipment (PPE) predict injuries. Methods: A community survey was conducted with 327 participants at 15 corners in Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…For example, immigrant workers on some poultry farms report that personal protective equipment (PPE) is often supplied by employers, but it may be up to the worker to purchase the equipment (82). In addition, workers themselves do not always follow safety rules, electing not to wear PPE due to poor fit or the belief that the equipment interferes with the work (5,26). For example, despite federal legislation requiring farmers to supply PPE, migrant workers in Australia's agricultural sector report low levels of compliance with wearing PPE (97).…”
Section: Working Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, immigrant workers on some poultry farms report that personal protective equipment (PPE) is often supplied by employers, but it may be up to the worker to purchase the equipment (82). In addition, workers themselves do not always follow safety rules, electing not to wear PPE due to poor fit or the belief that the equipment interferes with the work (5,26). For example, despite federal legislation requiring farmers to supply PPE, migrant workers in Australia's agricultural sector report low levels of compliance with wearing PPE (97).…”
Section: Working Conditionsmentioning
confidence: 99%
“…Safety trainings, posted safety information and warning signs, and legal information do little to protect workers if workers are unable to understand them (90). Trainings may be inadequate for the level of risk involved in the work (69), may not be available in the workers' primary language, and may present complicated information (26,43,55). Furthermore, factors such as social position or other cultural issues may impact how workers receive trainings presented by other workers, even if they speak the same language (28).…”
Section: Language and Cultural Barriersmentioning
confidence: 99%
“…Work-related factors that have been considered include a variety of physical and psychosocial working conditions. Several studies confirmed that dangerous work conditions, job stress, and high physical and mental workload were associated with work accidents and absence [10][11][12][13][14] .…”
Section: Introductionmentioning
confidence: 95%
“…6,12,13 However, adverse effects of occupational noise exposure usually occur in the range 80-85 dBA and > 85 dBA. Noise exposure level data were not available in the present study, but it is possible that the average noise level among this…”
Section: 42mentioning
confidence: 99%